Marketing Management and Distribution of Vannamei Shrimp at the Karangantu Fisheries Polytechnic Installation, Serang City - Yernawilis, Yernawilis; Mesenu, Mesenu; Zalmirosano, Zalmirosano; Indra Syamson; Harisjon, Harisjon; Agung D Anggoro; Ratih Martia Rahmani (Yayasan Insan Mulia Bima, 2026)
Vannamei shrimp (Litopenaeus vannamei) is one of the leading commodities in the Indonesian aquaculture industry due to its high productivity, relatively rapid growth, and strong adaptability to diverse environmental conditions. This study aims to analyse marketing management and distribution aspects of vannamei shrimp at the Karangantu Installation of the Polytechnic of Fisheries Business Expertise, Kasemen District, Serang City, Banten Province, with a focus on improving efficiency, competitiveness, and the sustainability of aquaculture enterprises. The research employed a descriptive method with a qualitative approach, conducted through field observations, in-depth interviews with relevant stakeholders, and analysis of secondary data related to production, marketing, and distribution. The findings indicate that the implementation of well-planned marketing strategies, supported by efficient distribution systems and integrated supply chain management, contributes significantly to increased productivity and profitability of vannamei shrimp farming. The study concludes that strengthening marketing management and distribution plays a strategic role in enhancing the performance and sustainability of aquaculture businesses. Furthermore, the findings provide educational contributions to the development of entrepreneurship learning and agribusiness management in vocational education, particularly in improving students’ competencies and encouraging managerial innovation towards sustainable aquaculture.